Analysis of Nutritional Status of Patients with Chronic Hepatitis - Sh.Ya.Zakirkhojaev; M.Kh.Talibdzhanova (Genius Journals, 2024)
"Evaluation of the nutritional status of patients with chronic liver diseases and their dietary correction"
Keywords: chronic liver diseases; nutritional status; diet therapy